Aqueous Colloid + Polymer Depletion System for Confocal Microscopy and Rheology - Park, Nayoung; Umanzor, Esmeralda J.; Conrad, Jacinta C. (Frontiers in Physics, 2018)
We developed a model depletion system with colloidal particles that were refractive index- and density-matched to 80 (w/w)% glycerol in water, and characterized the effect of interparticle interactions on the structure and dynamics of non-equilibrium phases. 2,2,2-trifluoroethyl methacrylate-co-tert-butyl methacrylate copolymer particles were synthesized following Kodger et al. (Sci. Rep. 5, 14635 (2015)). Particles were dispersed in glycerol/water solutions to generate colloidal suspensions with good control over electrostatic interactions and a moderately high background viscosity of 55 mPa-s. To probe the effects of charge screening and depletion attractions on the suspension phase behavior, we added NaCl and polyacrylamide (M_w = 186 kDa) at various concentrations to particle suspensions formulated at volume fractions of phi = 0.05 and 0.3 and imaged the suspensions using confocal microscopy. The particles were nearly hard spheres at a NaCl concentration of 20 mM, but aggregated when the concentration of NaCl was further increased. Changes in the particle structure and dynamics with increasing concentration of the depletant polyacrylamide followed the trends expected from earlier experiments on depletion-driven gelation. Additionally, we measured the viscosity and corrected first normal stress difference of suspensions formulated at phi = 0.4 with and without added polymer. The solvent viscosity was suitable for rheology measurements without the onset of instabilities such as secondary flows or edge fracture. These results validate this system as an alternative to one common model system, suspensions of poly(methyl methacrylate) particles and polystyrene depletants in organic solvents, for investigating phase behavior and flow properties in attractive colloidal suspensions.